Protestants Between Orthodoxy and Heterodoxy 1910 – 1940 (Theological Kronos, 2021)
The first-generation Protestants in Colombia allied themselves with anti-Catholic dissidents and formed a common association to fight for civil rights, the free exercise of worship and assembly. This Protestantism took a heterodox form in the first decades of the 20th century and was later changed by the imperative of evangelical unity that built its identity, converging towards an orthodoxy far removed from the relationships built in the first decades.
Keywords: Protestants; Dissidents; Civil rights; political; anti-Catholicism